REST-API Implementation for Optimizing Features in the K-Mob Jabar Smart ASN Application - Halizah, Nur; Azkiya Jamaludin, M. Rifqi (CV. Generasi Intelektual Digital, 2025)
The Jabar Smart ASN (JSA) application is a staffing application used to access other West Java Province staffing applications, one of which is the K-Mob application. The JSA application cannot be fully used, because there are still some features in K-Mob that are not optimal in accordance with the expected functions. So that from these problems, the implementation of REST-API on the features of the K-Mob application in Jabar Smart ASN is carried out. This research successfully implemented REST-API on the Working Hours, Claims and Appeals, and Recapitulation features with a response code of 200. However, the Subordinate Presence feature gave a response code of 500, caused on the server side. Although there are problems in the REST-API implementation process, the problems have been identified and can be the basis for further improvement.